Ultrasound and magnetic resonance imaging of hands in systemic sclerosis: A cross-sectional analytical study of prevalence of inflammatory changes in patients with subclinical arthropathy. Issue 1 (February 2023) - Babulal Vadher, Akash; Sinha, Anindita; Roy Choudhury, Shayeri; Prakash, Mahesh; Maralakunte, Muniraju; Rehman, Tanveer; Sharma, Shefali; Kumar, Yashwant
Objectives: Prevalence of synovitis, tenosynovitis, erosions, acro-osteolysis and bone marrow edema in systemic sclerosis is not extensively reported. We aimed to estimate the prevalence of changes in individual joints of hands in systemic sclerosis patients. Method: A cross-sectional analytical study consisting of 34 adults (females, n = 32) with systemic sclerosis. Patients with clinical synovitis were excluded. All patients underwent ultrasound (US) and magnetic resonance imaging of bilateral hands. Results: On US, synovitis, tenosynovitis, erosions, and acro-osteolysis were detected in 97%, 94%, 97%, and 29% patients. Grade I synovitis observed in 67% joints—first carpometacarpal joint (55%), first metacarpophalangeal joint (54%), distal radioulnar joint (50%), and intercarpal joints (47%) were commonly affected. Erosions were common in distal phalanges (first DP72% to fifth DP39%). On magnetic resonance imaging, synovitis, tenosynovitis, erosions, and bone edema were observed in 91%, 85%, 97%, and 85% patients. Grade I synovitis was seen in 70% joints, affecting intercarpal joint (70.6%) and third metacarpophalangeal joint (52.9%) commonly. Grade I erosions were seen in 61%, affecting distal phalanges (55.8%), capitate (60.3%), and lunate (55.8%). Grade I edema was commonly affecting lunate (39%) and capitate (26%). On magnetic resonance imaging, acro-osteolysis was present in 28% (97/340) distal phalanges. Fair agreement (0.21–0.40) was noted between US and magnetic resonance imaging for synovitis and erosions. Conclusion: High prevalence of low-grade inflammation is found in systemic sclerosis patients on US and magnetic resonance imaging. Distal joint assessment in addition to proximal joints improves accurate estimation of prevalence of early arthropathy.